PRODUCT PLACEMENT IN TOP 10 KOREAN DRAMA SERIES OF 2022: A CONTENT ANALYSIS - Cokki Cokki; Phuah Kit Teng; Jessica Maria Kusuma Miharja; Anisa Rizkika; Nanako Keisya Emanuella; Isabel Sekar Arum Wigati Binar Wulandari Kusumo (International Journal of Application on Economics and Business, 2026)
The Hallyu phenomenon which entered Indonesia through K-Dramas has positioned product placement as an important marketing communication strategy to influence brand awareness and consumer purchasing decisions. This study aims to analyze product placement strategies in the ten highest-rated K-Dramas of 2022 using quantitative content analysis approach. The analysis focuses on six main components: brand, placement type, character involvement, on-screen position, placement disclosure, and placement context. Data were collected from 122 episodes and analyzed to identify patterns of product placement. The findings indicate that product placements in 2022 K-Dramas generally emphasize products related to daily needs, visually presented through the involvement of main characters and integrated into the storyline without disclosure. Korean brands appeared more frequently than non-Korean brands in most dramas. In addition, product placements tend to appear in neutral contexts, with female characters more often associated with food and beverage as well as media and entertainment products, while male characters are more commonly linked to automotive products. These findings contribute academically to understanding product placement practices in the Korean entertainment industry and offer practical insights for the Indonesian entertainment sector in adopting similar strategies.